PENGEMBANGAN SERTA PENATAAN DALAM MENGELOLA SUMBER DAYA ALAM (SDA) PADA SEKTOR PARIWISATA DI DESA PARDOMUAN AJIBATA KABUPATEN SIMALUNGUN - Winfrontstein Naibaho; Ryan Tama F Purba Purba; Yohanson Sidabalok (Abdi Jurnal Publikasi, 2024)
One of the main causes that can cause environmental cleanliness problems is the lack of public concern for the environment. People should be aware and care about the environment around them because environmental conditions also affect people's lives themselves. The aim of this community service activity is to form an attitude of community awareness and community concern for the beauty and cleanliness of the environment by first socializing with the community to carry out mutual cooperation activities. The method used in this activity is a method of socializing the importance of cleanliness and beauty of the surrounding environment and inviting the public to take part in mutual cooperation activities that we are currently carrying out. Implementation of activities consists of several stages, namely: preparation, implementation and evaluation. Based on the results of the activity, it can be concluded that this activity can be said to be a success and the community around Parsaoran Village, Ajibata District, Toba Regency, is very enthusiastic about participating in collaborative activities, which is hoped that the community will care more about the cleanliness and beauty of tourisim.